Front Cover, Volume 2, Number 2, April 2023. Issue 2 (18th April 2023) - Van Assche, David; Beneyton, Thomas; Baret, Jean‐Christophe
Abstract : Front Cover : The cover image is based on the Research Article Rectifying jet breakup by electric forcing by Van Assche et al. Electric fields provide means to actuate droplet at high‐throughput in microfluidics. Using a modulated AC‐field, droplets are generated at high‐throughput in a jetting regime with improved monodispersity. (DOI: 10.1002/dro2.45 )